Modeling Biomass Saline Hydrolysis with Aspen Plus: a Study on Agro-industrial Waste Valorization - Bryan Santos Silva; Reginaldo Guirardello (Chemical Engineering Transactions)
Studies on energy matrices underscore the critical need to transition to sustainable energy sources, emphasizing diversification and the reduction of greenhouse gas emissions. This study uses Aspen Plus software to conduct research focused on the valorization of agro-industrial waste, specifically sugarcane derivatives, through the simulation of an industrial plant using the E-NRTL (Electrolyte Non-Random Two-Liquid) thermodynamic model. This model determines chemical equilibrium and component interactions in the saline hydrolysis of biomass. The proposed approach offers significant advantages: electrolytes facilitate the transformation of the crystalline biomass structure into amorphous forms, enhancing breakdown efficiency and minimizing product degradation during the reaction. Process simulations were conducted using Aspen Plus 8.7 software, based on literature data. Results show that optimal methods and operating conditions depend on the type of salt used. For annual sugarcane bagasse production of 4,000,000 kg, NaCl enables efficient biomass processing at concentrations of up to 20 % by mass, reducing salt consumption and mitigating separation challenges. Conversely, LiBr allows up to 30 % biomass concentration, but requires higher reagent and energy inputs.